Pengaruh Likuiditas, Solvabilitas dan Aktivitas Terhadap Kondisi Profitabilitas Pada PT Pan Brothers Tbk - Nurshifa Putri Irawan; Erna Herlinawati; Andre Suryaningprang; Yoyo Sudaryo (Journal Of Business, Finance, and Economics (JBFE), 2022)
The study aims to determine the impact of liquidity, solvency and activities on PT Pan Brothers Tbk's profitability for the period 2012-2021. The method used is a quantitative method with descriptive and confirmatory approaches. Data collection techniques using documented methods. The sampling technique used was targeted sampling. The data analyzes used are descriptive analysis, classical hypothesis testing, multiple regression analysis, correlation analysis, certainty analysis, and hypothesis testing. The results are as follows. 1) Liquidity (CR) is partially unaffected and not material to profitability (ROA). 2) Solvency (DER) is partially unaffected and not material to profitability (ROA). 3) Activity (TATO) has partial impact. Impact on Profitability (ROA) 4) Liquidity (CR), Solvency (DER) and Activity (TATO) all have a significant impact on profitability (ROA).